Advanced accounting - Jeter, Debra C.; Chanel, Paul K. (Hoboken, New Jersey : John Wiley & Son, Inc., 2012)
Delivers a balanced and detailed approach to the conceptual and technical aspects of advanced accounting * Features more in-depth information about international accounting, the upcoming globalization of accounting standards, changes with FASB's, and the latest developments and differences between U.S.
1 Introduction to Business Combinations and the Conceptual Framework -- 2 Accounting for Business Combinations -- 3 Consolidated Financial Statements-Date of Acquisition -- 4 Consolidated Financial Statements after Acquisition -- 5 Allocation and Depreciation of Differences between Implied and Book Values -- 6 Elimination of Unrealized Profit on Intercompany Sales of Inventory -- 7 Elimination of Unrealized Gains or Losses on Intercompany Sales of Property and Equipment -- 8 Changes in Ownership Interest -- 9 Intercompany Bond Holdings and Miscellaneous Topics-Consolidated Financial Statements -- 10 Insolvency-Liquidation and Reorganization -- 11. International Financial Reporting Standards -- 12 Accounting for Foreign currency Transactions and Hedging Foreign Exchange Risk -- 13 Translation of Financial Statements of Foreign Affiliates -- 14 Reporting for Segments and for Interim Financial Periods --- 15 Partnerships: Formation, Operation, and Ownership Changes -- 16 Partnership Liquidation.
Keywords: ACCOUNTING